THE IMPORTANCE OF HAVING AFTER CLASS ACTIVITIES IN THE DEVELOPMENT OF SCHOOL CHILDREN - Dustmuroova, Durdona Farkhod kizi; Khasanova, Yulduz Mukhtor kizi (Innovative Development in Educational Activities, 2024)
The purpose of the research paper is to investigate the impact of after-class activities on the development of children according to social, cognitive, interactive and emotional areas. To conduct this research 40 different aged students have been involved and divided into several extracurricular activity groups including art, music, craft and sport. Survey method has been utilized in order to know the responds of students. 10 questions have been prepared beforehand and half of them were asked firstly as the pre-test assessment and other half was asked at the end of the research as the post-test assessment. The analyses indicated significant improvements in different domains, for instance, the sport group showed enhanced physical fitness and teamwork skills. Art and craft activities were related to improved creativity and communication, musical activities showed their effect on children’s emotional well-being. The outcomes indicate that organizing after-school programs outside of school hours have positive impact and serve them develop their weak points and nurture their talents. So, educators, parents and government should recognize the significance of after-class activities and equip them with essential tools for their success.